Implications of Maslow’s Hierarchy of Needs Theory on Healthcare Employees’ Performance - Simona Cătălina Ștefan; Ștefan Cătălin Popa; Cătălina Florentina Albu (Transylvanian Review of Administrative Sciences, 2020)
The purpose of this study is to provide a new perspective of the motivation-performance link, and the influence of satisfying each basic human needs, described by Maslow’s hierarchy of needs, on employees’ professional performance. We assumed that the positive relationship between each dimension of motivation and professional performance is mediated by work satisfaction. The proposed conceptual model was operationalized by seven latent constructs (the five dimensions of motivation, inspired by the Maslow’s hierarchy of needs, job satisfaction and the professional performance), each of them measured by several observed indicators. The survey conducted for this occasion, was filled in by 824 employees from Romanian health organizations. Based on the research results, we can state that the Romanian health system employees are mostly motivated by meeting the needs of higher level, especially the need of self-actualization, and to a lesser extent by meeting the lower level ones. Those findings may serve as useful insights for health system policy makers and managerial practices in designing and implementing the most effective motivational strategies, able to generate increased professional performance.